Physical activity levels and predictors in patients following percutaneous coronary intervention: a cross-sectional study - Feng Xiao-Lin; Shang Shao-Mei; Xu Shun-Lin; Chen Hong-Bo; Wang Yun-Lin (Frontiers of Nursing, 2023)
To examine physical activity (PA) of post-percutaneous coronary intervention (PCI) patients and explore the demographic, clinical, and social psychological characteristics associated with PA levels.